A theology of testament in the young Luther the lectures on Hebrews - Hagen, Kenneth (Leiden, Netherlands E. J. Brill, 1974)
Includes bibliographical references and indexes.
Luther's "Lectures on Hebrews", 1517-18.
Keywords: Bible. N.T. Hebrews -- addresses, lectures, sermons -- criticism, interpretation, etc